A educação inclusiva na escola indígena Ebenezer do povo Tikuna da Comunidade de Filadélfia no município de Benjamin Constant-AM - Rodrigues, Darcimar Souza (2014)
This research paper discusses inclusive education in indigenous school education based on an indigenous school of the Tikuna people in Alto Solimões, AM. The focus of this paper are the students with special educational needs in the Ebenezer Municipal Indigenous School. It studies the issue of the influence of inclusive education in the indigenous educational context, from the perspective of their social communal interaction and the alternative pedagogical school practices. The bibliographic and documental research took place at the Ebenezer School of the Tikuna Indigenous Community of Filadélfia, in the municipality of Benjamin Constant, AM. This school was chosen because it is an indigenous school and is part of a municipality which has adopted inclusive education in the regular urban schools. The issues to be presented will refer to the learning problems and to the specialized educational service directed toward the students with special educational needs and the difficulties which the teachers have in relation to the education of students with special needs in their totality and the teaching conditions in the indigenous school faced with the proposal of inclusion. This study was carried out in a qualitative form and had as instrument of data collection a field diary in the form of an ethnographic study, institutional documents obtained from the Education Department of the municipality and from the school itself, which permitted a documental analysis based on concrete data. Based on this analysis it was observed that in the Ebenezer Municipal Indigenous School there is no work aimed at inclusive education. But one has perceived among the students attitudes of solidarity which walk in the direction of inclusion. However, it is important to point out that to attend to the diversity of the students, the school and the municipality will have to broaden their offer of resource rooms in the rural zones and invest more in continuing education for the teachers in such a way that the proposal of inclusive education may effectively arrive at the indigenous schools.